Acupuncture for COVID-19 patient after ventilator weaning: A protocol for systematic review and meta-analysis - Chi, Wenxin; Chen, Ying; Wang, Lina; Luo, Ziyu; Zhang, Yu; Zhu, Xiangyu (Medicine (Baltimore), 2020)
COVID-19 has spread globally since its outbreak in late 2019. It mainly attacks people's respiratory system. Many patients with severe COVID-19 require a ventilator to support breathing, and their lung function is often impaired to varying degrees after ventilator weaning. Acupuncture has been reported to improve respiratory function, but there is no evidence that it can improve respiratory function in ventilator users with COVID-19 after they are removed from the machine. The protocol of the systematic review and meta-analysis will clarify safety and effectiveness of acupuncture on respiratory rehabilitation after weaning from the ventilator during the treatment of COVID-19. We will search PubMed, EMBASE, MEDLINE, the Cochrane Library, Chinese National Knowledge Infrastructure, Chinese Biomedical Literature Database, Chinese Science and Technology Periodical Database, Wanfang Database, Clinical Trials and Chinese Clinical Trial Registry. Relevant English language and Chinese language literature will be included. A combination of subject words and free text words will be applied in the searches. The complete process will include study selection, data extraction, risk of bias assessment, and meta-analyses. We will use subgroup analysis and sensitivity analysis to explore the sources of heterogeneity if there is heterogeneity. We will use funnel charts to assess the risk of bias. Endnote X9.3 will be used to manage data screening. The statistical analysis will be completed by RevMan5.2 or Stata/SE 15.1 software. This study will assess safety and effectiveness of acupuncture for rehabilitation on respiratory function after weaning from the ventilator during the treatment of COVID-19. The conclusion of this study will give evidence to prove safety and effectiveness of acupuncture for rehabilitation on respiratory after weaning from the ventilator during the treatment of COVID-19. PROSPERO CRD42020206889.